2013
DOI: 10.1016/j.adolescence.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

What will I be when I grow up? The impact of gender identity threat on adolescents' occupational preferences

Abstract: The present study examined the impact of gender identity threat on adolescents' occupational preferences. Two hundred and ninety‐seven adolescents (45% girls, M age = 14.4, SD = .54) participated in the experiment. There were substantial differences between boys' and girls' occupational preferences. Importantly, adolescents who received a threat to their gender identity became more stereotypical in job preferences, suggesting a causal link between threatened gender identity and stereotypical preferences. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 53 publications
1
32
1
Order By: Relevance
“…Likewise, men are supposed to be more rational and mathematical and women more nurturing and verbal (Jacobs et al 2002;Parsons and Bales 1955). According to gender socialisation theories (Fagot, Rodgers, and Leinbach 2000), adolescents internalise these gender role expectations in their gender ideology and conform to the behavioural prescriptions of their gender category because doing so confirms their identity (Akerlof and Kranton 2000;Sinclair and Carlsson 2013). Similarly, not conforming to internalised gender role expectations leads to uncertainty and guilt, which they will try to avoid.…”
Section: Theorymentioning
confidence: 99%
“…Likewise, men are supposed to be more rational and mathematical and women more nurturing and verbal (Jacobs et al 2002;Parsons and Bales 1955). According to gender socialisation theories (Fagot, Rodgers, and Leinbach 2000), adolescents internalise these gender role expectations in their gender ideology and conform to the behavioural prescriptions of their gender category because doing so confirms their identity (Akerlof and Kranton 2000;Sinclair and Carlsson 2013). Similarly, not conforming to internalised gender role expectations leads to uncertainty and guilt, which they will try to avoid.…”
Section: Theorymentioning
confidence: 99%
“…Non‐US samples with females are less frequent, but do exist and show some notable results. In a recent study with Swedish eight‐graders (Sinclair & Carlsson, ) there were no gender differences in threat compensation, suggesting that further investigation of threat to feminine gender identity is warranted.…”
Section: Generalization Of Threat Compensation Effectsmentioning
confidence: 95%
“…To induce a threat to gender identity, we used a procedure that is based on ease of retrieval (see Schwarz, Bless, Strack, Klumpp, Rittenauer‐Schatka & Simons, ), and that has previously been used to induce gender identity threat (Sinclair & Carlsson, ; Weaver et al ., ). When retrieval from memory is facilitated, one generally concludes that the trait in question is common.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinclair and Carlsson (2013) found that there was a substantial difference in the occupational preferences of boys and girls and highlight that construction workers are predominantly male, and healthcare workers female. An Irish study using a quantitative design of time-use found that there were differences in how teenage boys and girls spent their time (Hunt et al, 2014).…”
Section: Gender and Adolescencementioning
confidence: 99%